PENGARUH PERUBAHAN TATAGUNA LAHAN TERHADAP KARAKTERISTIK HIDROGRAF BANJIR DI DAS MIU - Oktavia, Siti Rahmi; Amaliah, Tutty (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2017)
The Miu basin is one of the watersheds located in Sigi District, Central Sulawesi province with an area of 10,471,71 km2. In the last few years, Miu basin frequently got flood disaster and sediment. The change of watershed response to rain due to land use change is pointed to be the cause of frequent floods. It is necessary to overcome the frequent flooding in Miu basin by conducting hydrological analysis to determine the peak discharge change due to land use change. In this study, the analysis of the area ofÂ  rain with Polygon Thiessen Method was conducted with the help of ArcGIS 10.3 software. ArcGIS 10.3 software is also used to analyze land use change. The process of diversing the rain into a stream by calculating the effective rainfall (Peff) using the Soil Conservation Service-Curve Number (SCS-CN) Method. For Design Flood is calculated by the Nakayasu HSS Method. The research shows that the value of Curve Number as the determinant variable of land function change at Miu basin of 2003, 2009 and 2014 did not experience significant change. The decrease of flood peak discharge by HSS Nakayasu method in 2003, 2009 and 2014 respectively 525 m3 / sec, 366,4 m3 / second and 154,3 m3 / sec. The decrease in peak flood discharge is due to the fact that in addition to the non-significant land use change, the area rainfall as the input in the flood analysis of the designs of those years decreased from 2003 to 2014.Â